EKSPERIMENTASI MODEL PROBLEM BASED LEARNING (PBL) DAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) PADA MATERI DIMENSI TIGA DITINJAU DARI KEMAMPUAN BERPIKIR KREATIF SISWA (KBK) - Fadjrin, Nanda Noor; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract. The objective of this research was to investigate the effect of the learning models on achievement viewed from creative thinking abilities (CTA) of the students. The learning models compared were PBL, TGT and direct instruction (DI). The type of the research was quasi-experimental research with 3x3 factorial design. The population of this research was the students in grade X senior high school in Purbalingga on academic year of 2014/2015. The size of the sample was 277 students, which was taken by using stratified cluster random sampling technique. The instruments used for data collection were creative thinking test and achievement test. The hypothesis test used unbalanced two ways analysis of variance. The results of the research were as follows. (1) PBL gave better achievement than TGT and DI. TGT gave better achievement than DI. (2) The students with high and medium CTA had better achievement than the students with low CTA. The students with medium CTA had better achievement than the students with low CTA. (3) In PBL, the students with high CTA had better achievement than medium and low CTA, the students with medium and low had the same achievement. In TGT, the students with high and medium CTA had the same achievement, the students with high CTA had better achievement than low CTA, the students with medium and low CTA had the same achievement. In DI, the students with high, medium and low CTA had the same achievement. (4) At the students with high CTA, PBL and TGT gave the same achievement. PBL and TGT gave better achievement than DI. At the students with medium CTA, PBL and TGT gave the same achievement, PBL gave better achievement than DI, TGT and DI gave the same achievement. The students with low CTA, PBL, TGT and DI gave the same achievement.Keywords: Problem Based Learning, Teams Games Tournamnet, Direct Instruction, Creative Thinking Abilities , Achievement.